Cancer-Associated Fibroblast Density, Prognostic Characteristics, and Recurrence in Head and Neck Squamous Cell Carcinoma: A Meta-Analysis - Knops, Alexander M.; South, Andrew; Rodeck, Ulrich; Martinez-Outschoorn, Ubaldo; Harshyne, Larry A.; Johnson, Jennifer; Luginbuhl, Adam J.; Curry, Joseph M. (Frontiers in Oncology, 2020)
Introduction: The progression and clinical course of head and neck squamous cell carcinoma (HNSCC) relies on complex interactions between cancer and stromal cells in the tumor microenvironment (TME). Among the most abundant of these stromal cells are cancer-associated fibroblasts (CAFs). While their contribution to tumor progression is widely acknowledged, and various CAF-targeted treatments are under development, the relationship between CAF density and the clinicopathologic course of HNSCC has not been clearly defined. Here we examine the published evidence investigating the relationship of cancer-associated fibroblasts and indicators of prognostic significance in HNSCC. Methods: We conducted a meta-analysis of existing publications that compare the relationship between CAF density and clinically significant pathologic criteria of disease development (T stage, nodal positivity, clinical stage, vascular invasion, perineural invasion, Ki67 expression, and differentiation). Eighteen studies met the selection criteria, providing a total study population of 1342 patients. Forest plots and risk ratios were generated to illustrate overall relationships. Results: Higher CAF density within the tumor microenvironment is associated with advanced T stage, nodal infiltration, clinical stage, vascular invasion, perineural invasion, Ki67 expression, and differentiation (p < 0.05). Conclusions: Across multiple studies, increased CAF density is correlated with histopathological criteria of poor prognosis in HNSCC. These findings highlight that CAFs may play a pivotal role in HNSCC development and progression. Staining for CAFs may represent a valuable addition to current pathologic analysis and help to guide prognosis and treatment. Understanding the mechanisms by which CAFs reciprocally interact with cancer cells will be crucial for the rational design of CAF-targeted treatment of HNSCC.